PERENCANAAN DESAIN BOTTOM HOLE ASSEMBLY (BHA) DENGAN VARIASI OUTER DIAMETER (OD) STABILIZER PADA PEMBORAN BERARAH TIPE J DI SUMUR X - Berkah Hani; Aly Rasyid; Matthew Greenly Tamima (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
This study discusses the design planning of the Bottom Hole Assembly (BHA) in J-type directional drilling with a focus on the effect of variations in Outer Diameter (OD) and stabilizer position on the well trajectory characteristics. The method used is a drilling planning simulation using WellPlan software on Well X with variations in Outer Diameter (OD) of the stabilizer of 10¾”, 11”, and 12”, as well as variations in the distance of the stabilizer installation from the drill bit, while other drilling parameters are kept constant. The main evaluation parameters include Build Up Rate (BUR) and Dogleg Severity (DLS). The simulation results show that increasing the Outer Diameter (OD) of the stabilizer results in an increase in the Build Up Rate (BUR) value represented by the Equilibrium Build Rate (EBR). In addition, the stabilizer installed closer to the drill bit shows a higher trajectory angle formation capability. The results of this study indicate that the selection of the right Outer Diameter (OD) and stabilizer position plays an important role in controlling the well trajectory and can be used as a reference in planning the design of the Bottom Hole Assembly (BHA) in J-type directional drilling.